PENGARUH SELF-EFFICACY TERHADAP KEMANDIRIAN BELAJAR SISWA - Hanifah, Tania Nur; Mulyadi, Ajang; Tanuatmodjo, Heraeni (Universitas Pendidikan Indonesia, 2017)
AbstractThis study aims to describe the student's self-efficacy, student learning independence, as well as the effect of self-efficacy on the learning independence of class XI Accounting 2016/2017 academic year in Financial Accounting subjects at SMK Negeri 1 Bandung. This study uses descriptive and verification methods. Data collection techniques in the form of questionnaires distributed to the entire population of students of class XI Accounting 2016/2017 academic year at SMK Negeri 1 Bandung, amounting to 105 people. Questionnaire self-efficacy is composed of 28 item statements with 11 alternative answers and learning independence questionnaire composed of 19 statement items with 5 alternative answers. The normality test uses the Kolmogorov-Smirnov test formula and correlation analysis using the Pearson product moment formula. All data processing uses Microsoft Statistical Product and Service Solution (SPSS) software version 23.0. From the calculation of the t test, it is known that tcounttable, so it can be concluded that self-efficacy has a positive effect on the learning independence of class XI Accounting students in the 2016/2017 academic year in Financial Accounting subjects at SMK Negeri 1 Bandung.Keywords. self-efficacy; learning independence AbstrakPenelitian ini bertujuan untuk mengetahui gambaran self-efficacy siswa, kemandirian belajar siswa, serta pengaruh self-efficacy terhadap kemandirian belajar siswa kelas XI Akuntansi tahun ajaran 2016/2017 dalam mata pelajaran Akuntansi Keuangan di SMK Negeri 1 Bandung. Penelitian ini menggunakan metode deskriptif dan verifikatif. Teknik pengumpulan data berupa angket yang disebarkan kepada seluruh populasi siswa kelas XI Akuntansi tahun ajaran 2016/2017 di SMK Negeri 1 Bandung yang berjumlah 105 orang. Angket self-efficacy tersusun dari 28 item pernyataan dengan 11 alternatif jawaban dan angket kemandirian belajar tersusun dari 19 item pernyataan dengan 5 alternatif jawaban. Uji normalitas menggunakan rumus uji Kolmogorov-Smirnov dan analisis korelasi menggunakan rumus Pearson product moment. Seluruh pengolahan data menggunakan software Microsoft Statistical Product and Service Solution (SPSS) versi 23.0. Dari perhitungan uji t diketahui thitung>ttabel , sehingga ditarik kesimpulan bahwa self-efficacy berpengaruh postitif terhadap kemandirian belajar siswa kelas XI Akuntansi tahun ajaran 2016/2017 dalam mata pelajaran Akuntansi Keuangan di SMK Negeri 1 Bandung.Kata Kunci: self-efficacy; kemandirian belajar